The Palladium and Platinum distribution in porphyry Cu± Mo deposits - Sodnom Oyungerel; Jamsran Purevdorj (Geological Issues, 2023)
According to the previous studies to identify contents of PGE in porphyry Cu ± Mo deposits (Aksug, Sora, Zhireken of Russia, Erdenetiin Ovoo of Mongolia, etc.), we wanted to give short information to student who studies in the mining sector and especially tor the experts who works as a miner, geologist or explorer that may this is new association to geology sector. We included 4 deposits brief introduction, contents of the PGE (Pd and Pt) in the various granitoid host rocks, main condition to form Pd and Pt in the porphyry system as well as future of this study. Precious metal and associated element contents are reported tor ore samples, sulphide concentrates, and chalcopyrite-molybdenite flotation concentrates from porphyry Cu-Mo intrusions of Russia (Sora. Aksug and Zhireken) and Mongolia (Erdenetiin-Ovoo). Average PGE contents in rocks are 17 ppb Pd and 22 ppb Pt in the Aksug deposit, 13 ppb Pd and <10 ppb (detection limit) Pt in the Sora, 14 ppb Pd and 21 ppb Pt in the Erdenetiin-Ovoo and 18 ppb Pd and 28 ppb Pt in the Zhireken deposit. In general, the precious metal distribution in the studied deposits has no direct relationship with the alteration types. The Cu-Mo ratios are highest in the Aksug and Erdenetiin-Ovoo deposits and lowest in the Sora and Zhireken deposits. According to experimental studies, significant amounts of Pd and Pt can be transported as chloride complexes by hydrothermal fluids in highly oxidized (fO2/fS2), salinity (30 to >75 wt% alkali chlorides) and high temperature (400°C to >700°C) within the K-silicate alteration also their deposition process is related to the composition of parent magma. Platinum group elements dissolved as chloride complexes may be deposited in response to a reduction, pH increase, dilution or temperature decrease (Grammon et al., 1992). About the temperature and other conditions are not exactly same in the other deposits such as 300-500°C temperature in Aksug deposits while Skouries deposit is formed in the 380°C-480°C etc. It is obvious that chloride complexes are the one of the most important transporter of Pt and Pd in the hydrothermal fluids from previous studies. During the past 25 years, many scientists have studied this significant study in porphyry Cu-Mo deposits in the different regions of the world. Even though we have porphyry Cu-Mo deposits such as Oyu-tolgoi, Tsagaan-suvarga, Erdenetuin-oboo, Harmagtai, Bayan-Uul, Shuteen, Saran-Uul. Ariin-Nuur etc, we’ve not researched this study in our porphyry Cu-Mo deposits yet except Erdenetin- ovoo research which was studied by Russian experts about decades before. Furthermore, since we have a porphyry Cu-Mo deposits, we have to do research on precious metals deeply on our deposits and determine the Pd and Pt contents. May be this study’s outcome will increase our precious metals reserve.